Barsey Rhododendron Sanctuary, Sikkim - a Remote Sensing Approach - Maity, D.; Taha, S. O.; Tambe, S.; Maiti, G. G. (Indian Forester, 2006)
Barsey Rhododendron Sanctuary (BRS) was notified in 1998 by the Govt. of India specially to conserve the genetic diversity of Rhododendron species, situated within Sikkim Himalayas. The present study is an approach towards the presentation of geo-physical consequences as well as major floristic components. Total 11 maps and respective tables have been used specially to analyse the forest types, forest density, soil types, altitude, slope aspect etc. and to characterize the sanctuary. This sanctuary is still with maximum coverage of broad-leaved forests, but simultaneously soil erosion is moderate to high. BRS is a habitat to 30% (10 out of 37 speies) of Rhododendron at present known to Sikkim Himalaya. The study highlights the capability of remote sensing techniques for future planning, conservation and forest management.